Al-attas' Concept of Reality: Empirical and Non-Empirical - Zarkasyi, Hamid Fahmy; Arroisi, Jarman; Salim, Mohammad Syam’un; Taqiyuddin, Muhammad (KALAM, 2019)
The concept of 'reality' is one of the most debatable discourse by philosophers, especially between Western and Islamic philosophers. One of Muslim philosophers’ criticism which addressed to Western philosophy is their tendency to restrict the  only meaning of reality to empirical beings. That makes metaphysical beings like truth (haqīqah), reason (‘aql), revelation (wahy), also God to be reduced merely as ‘concept’ (grand narrative). Therefore, this paper would like to examine the Syed Muhammad Naquib al-Attas’ thought on ‘reality’. This study focuses on the classification of reality and the relationship between physical and metaphysical reality. This philosophical study was carried out with a descriptive and critical-analysis method among al-Attas' works. This study conclude that reality is not restricted to merely rational-empirical beings; but further to the metaphysical reality that affirms the existence of God and its relationship with nature and humans are also examined in it. This study concludes that reality; both physical and metaphysical are actually classified as objects of knowledge, which imply to the perception of human judgment on the 'truth value' of a being.